PREPARATION OF ERLOTINIB HYDROCHLORIDE - Dai, Ta Van; Thanh, Le Tat; Long, Pham Quoc; Thuy, Tran Thi Thu (Vietnam Journal of Science and Technology, 2015)
Erlotinib hydrochloride (Tarceva) is a targeted cancer therapy drug approved for treatment of non-small cell lung cancer (NSCLC), pancreatic cancer and several other types of cancer. An efficient and economical synthetic method of title compound from ethyl 3,4-dihydroxybenzoate is described in 6 steps with overall yield of 51 %.